2020
DOI: 10.1021/acs.biochem.0c00299
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Drugs Modulate Off-Target Protein Folding Landscapes Inside Cells

Abstract: The dynamic cytoskeletal network of microtubules and actin filaments can be disassembled by drugs. Cytoskeletal drugs work by perturbing the monomer–polymer equilibrium, thus changing the size and number of macromolecular crowders inside cells. Changes in both crowding and nonspecific surface interactions (“sticking”) following cytoskeleton disassembly can affect the protein stability, structure, and function directly or indirectly by changing the fluidity of the cytoplasm and altering the crowding and stickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…For the last two decades, [1] smFRET techniques have been extensively used to study the properties of molecular machines, [2] intrinsically disordered proteins (IDPs),[ 3 , 4 , 5 , 6 , 7 , 8 ] protein folding processes,[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] protein‐ligand[ 17 , 18 , 19 ] and protein‐nucleic acid interactions,[ 20 , 21 , 22 , 23 ] as well as other structure‐function relationships and dynamic processes. [ 24 , 25 , 26 ] SmFRET is a particularly powerful and versatile tool to gain molecular and mechanistic insights because of its high spatial resolution (2–10 nm) combined with a wide range of accessible timescales (ns‐minutes).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, [1] smFRET techniques have been extensively used to study the properties of molecular machines, [2] intrinsically disordered proteins (IDPs),[ 3 , 4 , 5 , 6 , 7 , 8 ] protein folding processes,[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] protein‐ligand[ 17 , 18 , 19 ] and protein‐nucleic acid interactions,[ 20 , 21 , 22 , 23 ] as well as other structure‐function relationships and dynamic processes. [ 24 , 25 , 26 ] SmFRET is a particularly powerful and versatile tool to gain molecular and mechanistic insights because of its high spatial resolution (2–10 nm) combined with a wide range of accessible timescales (ns‐minutes).…”
Section: Introductionmentioning
confidence: 99%
“…We found that actin depolymerization drugs, such as latrunculin A, made localization less biased to the periphery ( Figure 5 B), suggesting that actin may play a role in how these aggregates are localized. Yet, it has been shown that actin depolymerization drugs also reduce molecular crowding [ 41 ], suggesting that the observed change in localization in the presence of latrunculin A may correspond with changes in molecular crowding rather than a direct effect of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of chemical bonding, chemical reactivity, photochemistry, and quantum phenomena in materials trapped deep in the energy landscape provide still more challenges despite having been exploited technologically for decades. Likewise the fact that analogous theoretical issues arise in the study of biomolecules and in the active matter that makes up cells , motivates still more work.…”
Section: Prospectsmentioning
confidence: 99%